Effect of Head and Tongue Posture on the Pharyngeal Airway Dimensions and Morphology in Three-Dimensional Imaging: a Systematic Review - Sirwan Fernandez Gurani; Gabriele Di Carlo; Paolo M. Cattaneo; Jens Jørgen Thorn; Else Marie Pinholt (eJournal of Oral Maxillofacial Research)
Objectives: Natural head position is recommended to be optimal at cone-beam computed tomography acquisition. For standardization purposes in control of treatment outcome, it is clinically relevant to discuss, if a change of posture from natural head position may have an effect on the pharyngeal airway dimensions and morphology, during computed tomography, cone-beam computed tomography or magnetic resonance imaging acquisition. This was the aim of the present literature review study for purposes of valid evidence, which was hypothesized, to be present.